The mental health care system for children and adolescents in Greece: a review and structure assessment - Marchionatti, Lauro Estivalete; Schafer, Julia Luiza; Karagiorga, Vasiliki Eirini; Balikou, Panagiota; Mitropoulou, Andromachi; Serdari, Aspasia; Moschos, Giorgos; Athanasopoulou, Lilian; Basta, Maria; Simioni, André; Vicenzi, Julian; Kapsimalli, Efstathia; et al. (Frontiers in Health Services, 2024)
BackgroundThe mental health system in Greece faces challenges to complete its transition to a community-oriented model, having significant concerns for child and adolescent care due to lower coverage and service gaps. This component of the mental health system has not been comprehensively evaluated.MethodsWe conducted a review of the mental health care system for children and adolescents in Greece. For a field assessment, we directly collected data from mental health services to map availability and distribution. We analyzed the needs of human resources using professional register data and the national census.ResultsThe National Health Care Service (ESY, Εθνικό Σύστημα Υγείας) is the public health system in Greece, characterized by public governance but significant private participation. Although ESY aims for universal care, gaps in population coverage and high user fees create barriers to access. Embedded within ESY, the mental health system is shifting towards a community-oriented structure since the psychiatric reform. For children and adolescents, there is a developing framework for regionalization and community services, including day centers, inpatient facilities, outpatient departments, and school-based psychoeducational facilities. However, services lack coordination in a stepped care model. Patient pathways are not established and primary care rarely involves child mental health, leading to direct access to specialists. Services operate in isolation due to the absence of online registers. There is no systematic performance monitoring, yet some assessments indicate that professional practices may lack evidence-based guidelines. Our mapping highlighted a scarcity of public structures, with an unbalanced regional distribution and many underserved areas. Child and adolescent psychiatrists are predominantly affiliated with the private sector, leading to professional gaps in the public system.ConclusionsOur assessment identifies an established framework for a community-oriented, universally accessible mental health system, yet several barriers impede its full realization. These include an inconsistent primary healthcare system, a shortage of specialists in the public sector, imbalanced service distribution, lack of coordination among providers, underfunding, and absence of quality monitoring. We propose interventions to promote child and adolescent mental health in primary care, coordinate patient pathways, establish standards of care, and monitor performance.